Outward activity of multinationals by country of location - ISIC Rev. 4 (Edition 2017) (OECD Statistics on Measuring Globalisation, 2017)
This dataset comprises statistics on the outward activity of multinationals in manufacturing by country of location where total manufacturing contains figures on the activity of affiliates located abroad by host country in the total manufacturing sector or in the total business sector. It uses ISIC Rev. 4 (International Standard Industrial Classification) . Data are presented from 2007onwards